2016
DOI: 10.1088/1361-6498/37/1/1
|View full text |Cite|
|
Sign up to set email alerts
|

Individual external dose monitoring of all citizens of Date City by passive dosimeter 5 to 51 months after the Fukushima NPP accident (series): 1. Comparison of individual dose with ambient dose rate monitored by aircraft surveys

Abstract: Date (d@'te) City in Fukushima Prefecture has conducted a population-wide individual dose monitoring program after the Fukushima Daiichi Nuclear Power Plant Accident, which provides a unique and comprehensive data set of the individual doses of citizens. The purpose of this paper, the first in the series, is to establish a method for estimating effective doses based on the available ambient dose rate survey data. We thus examined the relationship between the individual external doses and the corresponding ambi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 8 publications
4
34
0
Order By: Relevance
“…In response to major public concerns over radiation exposure in radiation-contaminated areas, government authorities, public utilities, and private companies initiated individual external and internal radiation monitoring to establish and implement a resilient radiation protection and safety program [2,3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to major public concerns over radiation exposure in radiation-contaminated areas, government authorities, public utilities, and private companies initiated individual external and internal radiation monitoring to establish and implement a resilient radiation protection and safety program [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Except for dose reconstruction estimation with scientific assumptions [12,13], most of these evaluations were based on voluntary-based radiation monitoring administered by local authorities, using an individual radiation dosimeter for determining the external exposure level [3,14,15] or anthropogammametry (i.e., whole body counting (WBC) for determining the amount of radionuclides within the body at the time of monitoring) [16,17,18,19]. In summary, as a result of the counter-dose measures as well as natural removal phenomena such as weather and radioactive decay [6], the current exposure risks from radiation in the environment (attributable to the Fukushima incident) is considerably low or at undetectable levels [20], implying a marginal risk of radiation-associated physical health consequences of the incident [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In Figs 2 Top (Bottom), isodose lines for an annual additional effective dose of 1 mSv for 3 (5) years after the accident are overlaid on the 8 th (10 th ) airborne monitoring map. The 1 mSv isodose lines shown in blue are the recalculated UNSCEAR estimate, and the contours in red are the 1 mSv isodose line estimated from the airborne monitoring results, converted to annual effective dose rates with the factor c = 0.15.…”
Section: Resultsmentioning
confidence: 99%
“…After the FDNPP accident, an airborne monitoring method has been established and carried out regularly [7], and the ambient dose equivalent rates have been released as maps and numerical data [8]. Using the data of the large-scale individual dose monitoring conducted by Date City, Fukushima Prefecture, Miyazaki et al [5] found that the personal dose equivalent (≈ the effective dose) monitored by glass-badges, and the ambient dose equivalent of the residential area from airborne monitoring are closely correlated. They also published the GIF animation published on the website at the same time, isodose lines for an annual additional effective dose ab extra in the 1 st , 3 rd , 5 th , 10 th , 30 th and 50 th years after the accident were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted spatial averaging of the walk survey data around each airborne data point improves the correlation significantly to the correlation coefficients of 0.96-0.99. Several studies have found that the airborne survey data are consistently higher than co-located ground-based measurements (Naito et al, 2014;NRA, 2014;Yamashita and Itabashi, 2015;Miyazaki and Hayano, 2016;Wainwright et al, 2017;Kinase et al, 2017). To account such systematic shift in Fig.…”
Section: Resultsmentioning
confidence: 95%